Principle And Practice In Applied Linguistics - Cook, Guy; Seidlhofer,Barbara (N Y Oxford University Press, 1995)
Principle and Practice in Applied Linguistics provides a comprehensive overview of the many and diverse areas in applied linguistics today. The papers range from second language acquisition to discourse analysis, corpus linguistics, and classroom practice; together they emphasize the reciprocal relationship of principle and practice, and the interdisciplinary nature of applied linguistics.
Keywords: Applied Linguistics